The Effect of Training and Education on the Performance of State Civil Apparatus (Survey on the Regional Civil Service Agency of West Java Province) - Garnasadya, Gaffar; Gurawan Dayona Ismail (Dinasti Publisher, 2024)
The Influence of Training and Education on the Performance of Civil Servants at the Regional Personnel Agency of West Java Province. This research examines the effect of training and education on the performance of civil servants at the Regional Personnel Agency of West Java Province. The primary objective is to assess how these factors enhance employee performance. A quantitative approach was utilized, employing a survey method with data collected through questionnaires distributed to 100 employees. The findings indicate that both training and education have a significant positive impact on employee performance, with an average performance increase of 20% observed after participating in training programs. The results highlight that effective training and educational initiatives not only improve individual skills and knowledge but also contribute to the overall efficiency and effectiveness of the organization. This study emphasizes the necessity for ongoing professional development for civil servants and offers recommendations for enhancing training programs to cultivate a more skilled and productive workforce.